2013
DOI: 10.5335/rbca.2013.2816
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on aspects that influence the sense of presence in virtual environments

Abstract: Resumo: Um dos objetivos e vantagens da Realidade Virtual é a promoção da sensação de "estar lá", de estar presente. As pesquisas existentes focaram em determinar "se" um fator contribui para o senso de presença. Este artigo compara dois sistemas de visualização, avaliando qual dos dois contribui mais para este senso. Dois sistemas de baixo custo e baixa tecnologia foram usados: estereoscopia anáglifa e campo de visão (FOV) largo (50º). O Questionário SUS foi aplicado a 63 participantes para avaliar o senso de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Hounsell, Kemezinski, and Schlindwein (2013) compared anaglyph-based stereoscopy and large field-of-view versions of a guided tour on a virtual university campus and found that stereoscopy increased users' level of spatial presence compared with the NS images. Furthermore, they claimed that using stereoscopy is an essential step to increase immersion in VR environments (Hounsell et al, 2013). Not all studies find positive results for stereoscopic presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Hounsell, Kemezinski, and Schlindwein (2013) compared anaglyph-based stereoscopy and large field-of-view versions of a guided tour on a virtual university campus and found that stereoscopy increased users' level of spatial presence compared with the NS images. Furthermore, they claimed that using stereoscopy is an essential step to increase immersion in VR environments (Hounsell et al, 2013). Not all studies find positive results for stereoscopic presentations.…”
Section: Introductionmentioning
confidence: 99%